Risalah al-islah : ru'yah fi al-manhaj wa al-shurut - al-Shaykh, Badawi Mahmud (al-Qahirah : Dar al-Salam, 1997)
On religious reform, for the general reader
Includes bibliographical references.
Keywords: Islamic renewal; Islamic fundamentalism